The circular economy for food in future cities. Good practices that define Smart Food - Franco Fassio; Elisa Cionchi; Alice Tondella (Agathón)
Food, a basic unit of connection among all SDGs, plays an essential role in the transition towards a sustainable development. This essay makes its scientific contribution to define both the theoretical-practical framework where the Circular Economy for food is developing and, in particular, its application to the urban context. When the population increases, the resources demand increases in the urban areas too, and environmental problems and socio-economic differences among citizens emerge. The analysis originates from 27 case histories concerning the food system, selected in order to represent the circular business models emerging from urban contexts and differing in the several steps of the food supply chain. Nine of them are closely studied in this essay to make the analysis clearer. A so-called Smart Food framework emerges, where the urban circular economy communicates with sustainable development in a systemic and regenerative way.